209k views
0 votes
Solve the equation: -3(h+5)+2=4(h+2)-9

User Wrufesh
by
5.9k points

2 Answers

3 votes

Answer:


h=-(12)/(7)

Explanation:

To solve the equation for h follow the next steps


-3(h+5)+2=4(h+2)-9

Subtract 4(h+2) on both sides of the equality


-3(h+5)+2-4(h+2)=4(h+2)-4(h+2)-9


-3(h+5)+2-4(h+2)=-9

Subtract 2 on both sides of the equality


-3(h+5)+2-4(h+2)-2=-9-2


-3(h+5)-4(h+2)=-11

Apply the distributive property


-3h-15 -4h-8=-11


-7h-15 -8=-11


-7h-23=-11

Sum 23 on both sides of equality


-7h-23+23=-11+23


-7h=12

Divide by -7 on both sides of the inequality


(-7)/(-7)h=-(12)/(7)


h=-(12)/(7)

User Celius Stingher
by
5.8k points
4 votes

For this case we must solve the following equation:


-3 (h + 5) + 2 = 4 (h + 2) -9

We apply distributive property to the terms of parentheses:


-3h-15 + 2 = 4h + 8-9

We add similar terms:


-3h-13 = 4h-1

We add 13 to both sides of the equation:


-3h = 4h-1 + 13\\-3h = 4h + 12

Subtracting 4h on both sides of the equation:


-3h-4h = 12\\-7h = 12\\h = - \frac {12} {7}

ANswer:


h = - \frac {12} {7}

User Mechanic
by
6.1k points